Isolation and identification of bioflocculant -producing bacteria from cassava cultivated soil in Vietnam - Hong, Tran Thi; Cường, Phạm Việt (Vietnam Journal of Science and Technology, 2021)
Microorganisms are found everywhere in the environment and play a leading role in countless natural processes, and amongst them, soil microorganisms play important roles in plant performance by improving mineral nutrition. Soil bacteria possess different biological activities; for example, producing bioactive compounds such as bioflocculant which makes soil smoother and more breathable, as plant growth stimulants or compounds with antibiotic activity. Beside this, the same soil bacteria could also be able to fix atmospheric nitrogen, converting it into the form that plants can use. In order to make a microbial formula from local bacteria capable of producing bioflocculant as well as IAA and fixing nitrogen towards microbial organic fertilizer production for application in cassava cultivation, the bacteria were isolated from cassava cultivated soils and screened for above mention activities. From 37 cassava root and cassava cultivated soil samples collected at different provinces in the North, Central and South regions of Vietnam, 80 strains of bacteria with bioflocculant activity over 50% were screened. In which 3 strains (ĐQT1 Po6, ĐTAN6 Po2 and ĐSBV Po1) possess not only high bioflocculant and IAA producing capacities, but also the ability to fix atmospheric nitrogen. The flocculant rate of these strains was 80÷90% and can produce 6÷11 µg/mL IAA. The selective strains were identified by having an analysis of 16S rRNA gene sequence. The obtained results showed that the 16S rRNA sequence of ĐQT1 Po6 was 100% identifiable to corresponding sequence of Bacillus aryabhattai FORT 21 (Ass.No MG561348.1); and the 16S rRNA sequences of ĐTAN6 Po2 and ĐSBV Po1 had 100% homology with those of Enterobacter sp. (Ass.No KJ184880.1) and Bacillus subtilis SAN1.5 (Ass.No KX098457.1), respectively. These strains are potential candidates as perfect inoculant for biofertilizer.